The church, poverty and public theology in Africa: - Hassan Musa (African Theological Journal for Church and Society)
The problem of poverty in African contexts is a pervasive one. It continually confronts the Church and society with serious questions on how best to address the problem. There are no easy answers, but that does not mean that there is nothing at all to say concerning it. It could be historically necessary to reflect on what the leading missionary enterprises did to Africa when they came with the gospel within a colonial administration. There were instances in which they were almost oblivious about the plight of the African people as long as the people to whom they presented the gospel would accept it and obey the rules of the church and biblical teaching. Little or nothing was done to address the poverty situation in which the African people suffered and died. But in recent years we have seen some paradigmatic shifts in the sense that many of the so-called mainline churches are now beginning to be open to the sociopolitical dimension of life in Africa. The contribution of the African theologian Samuel W. Kunhiyop will be discussed below to bring him to the centre of the dialogue on the church and poverty in Africa. The reception of the ‘theological-logic’ of Russel Botman of South Africa alongside other voices of ethical concern will also be closely considered. This essay aims to argue for the responsibility of the church in Africa to intentionally address the economic, political and ecological problems that continue to challenge the problem of poverty in Africa. This would be a call to the Church in Africa to be active and innovative in presenting a holistic gospel that is mindful of the spiritual, academic and social situation of people in different contexts. The article serves as an introduction to how Christians would hopefully continue to interpret the Bible in responsible and constructive ways.